Empowerment of Aisyiyah Orphanage Community-Based Padang Panjang Through Batik Training - Hadiarni Hadiarni; Zulhermindra Zulhermindra (Jurnal Masyarakat Religius dan Berwawasan, 2022)
This trial activity aims to empower the children of the Aisyiyah Padang Panjang Orphanagethrough batik training. To achieve the above objectives, the method used is Participatory Action Research(PAR). There are 3 main activities carried out, namely preparation, implementation, and evaluation.Preparation deals with coordination and FGD with the boards and caretakers of the orphanage related to theactivity plan and schedule for its implementation. Implementation of activities concerns with the mainempowerment activities, which include: a) initial introduction to batik materials, b) pattern making, c)painting, d) stamping, e) coloring and f) sag. This activity takes place at the Padang Panjang AisyiyahOrphanage every Saturday and/or Sunday from March 14, 2021 to April 9, 2021 with a total of 20participants. Evaluation aims at investigating participant satisfaction with the implementation of this serviceactivity. The results of the evaluation showed that 63.5% of the participants were very satisfied, 33% weresatisfied and 3.5% were quite satisfied and 0% were not satisfied